Demographic Predictors of Parenting Self-Efficacy Public Elementary School - John Mark Asio (Research Synergy Foundation, 2025)
Parenting self-efficacy (PSE) refers to the idea and ability to progressively enhance a child’s development and educational outcomes. It is crucial because it directly impacts a child’s academic performance, behavior, and overall well-being. Thus, the main objective of this study was to explore parents’ parenting self-efficacy in a selected public school in a province in the Philippines. The investigator employed a cross-sectional research design and collected data using a standardized instrument among 130 volunteer respondents. The collected data were analyzed by descriptive and inferential statistics using SPSS 23. The result revealed that based on the demographics, most respondents have 2-3 children, were married, unemployed, high school graduates, and had a monthly household income of 5001–10,000 pesos. For parenting self-efficacy (PSE), four constructs garnered a response of